Word Order in Turkish - Özsoy, A. Sumru; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This volume is a collection of studies on various aspects of word order variation in Turkish. As a head-final, left-branching 'free' word order language, Turkish raises a number of significant theory-internal as well as language-particular questions regarding linearization in language. Each of the contributions in the present volume offers a fresh insight into a number of these questions, thus, while expanding our knowledge of the language-particular properties of the word order phenomena, also contribute individually to the theory of linearization in general. Turkish is a configurational language. It licenses constructions in which constituents can occur in non-canonical presubject as well as postverbal positions. Presented within the assumptions of the generative tradition, the discussion and analyses of the various aspects of the linearization facts of the language offer a novel treatment of the issues therein. The authors approach the word order phenomena from a variety of perspectives, ranging from purely syntactic treatments, to accounts as syntax-PF interface or syntax-discourse interface phenomena or as output of base generation.
Introduction; A. Sumru Özsoy -- Part I: The Syntax of Word Order -- How to Derive the Directionality of Verb Ellipsis in Turkish Coordination from General Word Order; Jaklin Kornfilt -- On the Ban on Postverbal Wh-phrases in Turkish Syntax; Selçuk İşsever -- Eliminating Scrambling: The Variation of Word Order in Turkish; Serkan Şener -- Derivation of Fronting Constructions in Turkish: Feature Cyclicity or Cyclic Linearization; A. Sumru Özsoy -- Word Order and Syntactic Types; Cem Bozşahin -- Part II: Word Order and Syntax-Phonology Interface -- (Prosodic-)structural Constraints on Gapping in Turkish; Aslı Göksel and Aslı Gürer -- Towards a model of the relation between prosodic structure and object displacement in Turkish; Mine Nakipoğlu -- Part III: Word Order and Discourse Structure -- Discourse Structure: The view from Shared Discourse Units in Turkish Discourse Bank; Deniz Zeyrek.
Keywords: Grammar, Comparative and general -- Syntax; Oriental languages; Psycholinguistics; Syntax; Oriental or Semitic Languages; Psycholinguistics and Cognitive Lingusitics